PEMANFAATAN SEMIOTIKA VISUAL UNTUK MEMAHAMI KARYA SENI RUPA - Hendri, Zulfi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
<img src="data:image/png;base64,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